Contributions of poroelastic rebound and a weak volcanic arc to the postseismic deformation of the 2011 Tohoku earthquake - Wang, Kelin (2015)
A better understanding of fluid-related processes such as poroelastic rebound of the upper crust and weakening of the lower crust beneath the volcanic arc helps better understand and correctly interpret the heterogeneity of postseismic deformation following great subduction zone earthquakes. The postseismic deformation following the 2011 Mw9.0 Tohoku earthquake, recorded with unprecedented high resolution in space and time, provides a unique opportunity to study these ‘second-order’ subduction zone processes. We use a three-dimensional viscoelastic finite element model to study the effects of fluid-related processes on the postseismic deformation. A poroelastic rebound (PE) model alone with fluid flow in response to coseismic pressure changes down to 6 and 16 km in the continental and oceanic crusts, respectively, predicts 0 to 6 cm uplift on land, up to approximately 20 cm uplift above the peak rupture area, and up to approximately 15 cm subsidence elsewhere offshore. PE produces up to approximately 30 cm of horizontal motions in the rupture area but less than 2 cm horizontal displacements on land. Effects of a weak zone beneath the arc depend on its plan-view width and vertical viscosity profile. Our preferred model of the weak sub-arc zone indicates that in the first 2 years after the 2011 earthquake, the weak zone contributes to the surface deformation on land on the order of up to 20 cm in both horizontal and vertical directions. The weak-zone model helps eliminate the remaining systematic misfit of the viscoelastic model of upper mantle relaxation and afterslip of the megathrust.